Ibn Ashur’s Views on Maqasid al-Quran: An Analysis - Islam, Tazul (Maʿālim al-Qurʾān wa al-Sunnah, 2018)
This research deals with MuÍammad al-ÙÉhir Ibn Ashur’s (1879-1973 C.E.) views of Objectives (Maqasid) of the Quran. As one of the pioneers of the theory of maqasid al-Shariah, he pays a significant attention to this subject. Unlike other contributors to this subject, he identifies eight basic objectives of the Quran and implicates them to the Quranic exegesis. According to him, bringing objectives of the Quran perspective to the interpretation of the Quran is extremely necessary. This study is a library research in which the data were collected from Ibn Ashur’s writings as well as some other relevant literature. Dealing with the collected materials, the researcher made a discourse analysis of Ibn Ashur’s views on the mater. After each ‘objective’ is discussed, a brief focus is made on the methodological basis of his identification of Objectives of (Maqasid) the Quran instead of outlining the issues that he has identified as the main objectives (Maqasid).